Curing Kinetics and Thermal Properties of Aromatic Multifunctional Epoxy Resins. Issue 1 (January 2014) - Yu, Mingming; Zhou, Zhengwei; Lu, Hang; Li, Aijun; Bai, Ruicheng; Sun, Jinliang; Ren, Musu; Hu, Hefeng
In order to investigate the relationship between the chemical structure of multifunctional epoxy resins and their properties, two tetrafunctional epoxies with different aromatic rings content in the molecular main chain, N, N, N', N'-tetraglycidyl-4, 4'-diaminodiphenyl ether (4, 4'-TGDDE) and N, N, N', N'-tetraglycidyl-2, 2-bis[4-(4-aminophenoxy)phenyl]propane (TGBAPP), were cured with 4, 4'-diaminodiphenyl ether (4, 4'-DDE) and 2, 2-bis[4-(4-aminophenoxy)phenyl]propane (BAPP), respectively. Then four amine curing systems (TGBAPP/BAPP, TGBAPP/4, 4'-DDE, 4, 4'-TGDDE/BAPP and 4, 4'-TGDDE/4, 4'-DDE) were obtained. Additionally, the 4, 4'-TGDDE and another TGDDE with m-glycidyl amino, named N, N, N', N'-tetraglycidyl-4, 4'-diaminodiphenyl ether (3, 4'-TGDDE) were cured with methyl nadic anhydride (MNA). Then the anhydride curing systems (4, 4'-TGDDE/MNA and 3, 4'-TGDDE/MNA) were prepared. The curing kinetics and thermal properties of these systems were studied in detail. The results indicated that the anhydride curing systems exhibited higher curing reactivity than the amine curing systems, and the resins cured with the anhydride showed better thermal properties. Moreover, introducing more aromatic rings into the backbone would decrease the curing reactivity but enhance the thermal property of the multifunctional epoxy resins. And the tetrafunctional epoxy with p-glycidy amino groups had higher curing reactivity than the epoxy with p-glycidy amino groups, and the thermal property of the front epoxy was better.